Design and Implementation of a Fire Fighting System for a High-Rise Residential Building: A Case Study of SAMA Tower - Amer, Mohammed; Yaghmour, Jihad (Palestine Polytechnic University, 2025)
This paper describes the design and installation of a fire-fighting system in a high-rise building, the SAMA Residential Tower. A sprinkler system, a standpipe system, a fire hose cabinet, a landing valve, hydrants externally connected, and a Siamese connection are all included in this system. Additionally, it complies with the codes of NFPA 13, 14, and 20, as well as those of the Palestinian and Jordanian governments. A hydraulic calculation was performed manually and then confirmed using Elite Fire Protection software. The layouts were developed using AutoCAD, and the 3D modeling was created in Revit in order to optimize the placement of the components. All zones of the building will be protected by this integrated approach, which ensures reliable flow, sufficient pressure, and code compliance.
Number of pages: 6, 2025 Engineering for Palestine Conference (ENG4PAL) PPU, Hebron, Palestine, September 29-30, 2025
Keywords: Fire-fighting system, High-rise residential building, NFPA standards, Fire protection design.